Molecular characterization of the cysJIH promoters of Salmonella typhimurium and Escherichia coli: regulation by cysB protein and N-acetyl-L-serine. - Ostrowski, J (1989)
The cysJIH promoter regions from Salmonella typhimurium LT7 and Escherichia coli B were cloned and sequenced. Primer extension analyses showed that the major in vivo transcription initiation site in S. typhimurium is located 171 nucleotides upstream of the cysJ start codon. Minor start sites were found 8 and 9 nucleotides downstream of the major site. In vivo transcription initiation in E. coli was found to occur at a single site 66 nucleotides upstream of the cysJ start codon. Primer extension studies also indicated that chromosomal cysJIH transcription is stimulated by sulfur limitation and repressed by growth on L-cystine. Paradoxically, in strains carrying plasmids containing the S. typhimurium cysJIH region, the highest levels of primer extension products were found with RNA from cells grown on L-cystine, even though levels of the proteins encoded by cysJ and cysI were normally repressed. In vitro transcription runoff studies with DNA template from the S. typhimurium cysJIH promoter region showed synthesis of a product originating at the major in vivo start site, which was dependent on the presence of purified cysB protein and either O-acetyl-L-serine or N-acetyl-L-serine. N-Acetyl-L-serine was 10- to 30-fold more active than O-acetyl-L-serine as an in vitro inducer of cysJIH transcription.